2009
DOI: 10.1002/jqs.1350
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the human record in the British early Palaeolithic: evidence from the Solent River system

Abstract: The lithic record from the Solent River and its tributaries is re-examined in the light of recent interpretations about the changing demography of Britain during the Lower and early Middle Palaeolithic. Existing models of the terrace stratigraphies in the Solent and its tributary areas are reviewed and the corresponding archaeological record (specifically handaxes) for each terrace is assessed to provide models for the relative changes in human occupation through time. The Bournemouth area is studied in detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
67
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 39 publications
4
67
1
Order By: Relevance
“…Westaway et al (2006) also note the presence of Levallois artefacts at Kimbridge and Dunbridge, shown on their long profile as correlating with their Belbins Terrace. However, this age model has recently been challenged by Ashton and Hosfield (2009) on two grounds. Firstly, the age used for first occupation of southern Britain is based on a reinterpretation of the age of deposits at Pakefield that Ashton and Hosfield (2009) believe to be erroneous.…”
Section: Terrace Correlation In Relation To Age Estimatesmentioning
confidence: 99%
See 3 more Smart Citations
“…Westaway et al (2006) also note the presence of Levallois artefacts at Kimbridge and Dunbridge, shown on their long profile as correlating with their Belbins Terrace. However, this age model has recently been challenged by Ashton and Hosfield (2009) on two grounds. Firstly, the age used for first occupation of southern Britain is based on a reinterpretation of the age of deposits at Pakefield that Ashton and Hosfield (2009) believe to be erroneous.…”
Section: Terrace Correlation In Relation To Age Estimatesmentioning
confidence: 99%
“…However, this age model has recently been challenged by Ashton and Hosfield (2009) on two grounds. Firstly, the age used for first occupation of southern Britain is based on a reinterpretation of the age of deposits at Pakefield that Ashton and Hosfield (2009) believe to be erroneous. Secondly, Ashton and Hosfield (2009) argue that the low number and insecure provenance of Levallois artefacts in the Solent region make this an insecure tie-point to use in dating these sequences.…”
Section: Terrace Correlation In Relation To Age Estimatesmentioning
confidence: 99%
See 2 more Smart Citations
“…White 2000). Moreover, when likewise using extant distribution maps to investigate demographic patterns, Ashton and Hosfield (2010) and Davies (2013) have demonstrated that numbers of rolled handaxes increase the lower down a given terrace staircase (in this instance, the Solent) is sampled.Conversely, plateau and interfluve contexts cannot receive artefacts from higher, earlier eroding points in the landscape, relying, therefore, on people to deposit artefacts there. The assemblages recovered from them are sealed by fine-grained sediments (eg.…”
mentioning
confidence: 99%